Социологическая интерпретация инфраправа - Бова, А. (Социология: теория, методы, маркетинг, 2001)
The article presents the sociological interpretation of the infra-law as social institution. There are discussed theoretical aspects of the infra-law category and the terms characterized by close meanings. There are studied preconditions of the infra-law emergence and its status in the current Ukrainian society.